1999
DOI: 10.1067/msy.1999.98753
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a central role for p38 map kinase induction of tumor necrosis factor [alpha ] in pancreatitis-associated pulmonary injury

Abstract: p38 MAP kinase-induced TNF alpha production plays a central role in the development of pulmonary dysfunction, which accompanies severe acute pancreatitis in this rodent model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
46
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 0 publications
2
46
0
Order By: Relevance
“…Norman et al [7] found in SAP rats a positive correlation between the TNF-α concentrations in pancreatic tissue and plasma and the level of pancreatic injury and inflammation, which is consistent to the fact that in this experiment, the pancreas pathological score was positively correlated with TNF-α at 12 h in model group (P < 0.05). It was found in this experiment that the serum TNF-α contents were lower …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Norman et al [7] found in SAP rats a positive correlation between the TNF-α concentrations in pancreatic tissue and plasma and the level of pancreatic injury and inflammation, which is consistent to the fact that in this experiment, the pancreas pathological score was positively correlated with TNF-α at 12 h in model group (P < 0.05). It was found in this experiment that the serum TNF-α contents were lower …”
Section: Discussionsupporting
confidence: 74%
“…TNF-α can increase the local tissue damage and capillary permeability, eventually aggravating pancreatic necrosis, which is important in AP [7,8] . Norman et al [7] found in SAP rats a positive correlation between the TNF-α concentrations in pancreatic tissue and plasma and the level of pancreatic injury and inflammation, which is consistent to the fact that in this experiment, the pancreas pathological score was positively correlated with TNF-α at 12 h in model group (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of p38 MAPK decreases LPSinduced neutrophil influx, release of cytokines in the airspaces or serum, and expression of matrix metalloproteinase-9 in the airspaces (12,49,50). In two murine models of pancreatitis-induced lung injury, pretreatment with a p38 MAPK inhibitor reduced TNF-␣ release in the airways and reduced leukocyte accumulation, serum nitrites, and pulmonary edema (51,52). In an ischemia and reperfusion model of pulmonary injury, a p38 MAPK inhibitor decreased serum cytokine release and lung damage, but improved oxygenation (53).…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous research which demonstrated that administration of specific TNF-α and IL-1β inhibitors prevents I/R-related remote organ injury [22][23][24][25][26][27] . Furthermore, there is good evidence that agents which decrease distant lung injury after I/R also decrease pulmonary TNF-α 20,28,29 . As the specific objective of this study was to compare lung damage between groups subjected to normothermic and hypothermic renal ischemia, it was decided that the absence of a sham group would not affect analysis or interpretation of results.…”
Section: Discussionmentioning
confidence: 99%